Celebrity Bromances Constructing, Interpreting and Utilising Personas - Lam, Celia (Routledge Research in Cultural and Media Studies, 2022)
This comprehensive work presents a thorough exploration of celebrity 'bromances,' interrogating how bromances are portrayed in media and consumed by audiences to examine themes of celebrity persona, performativity, and authenticity. The authors examine how the performance of intimate male friendships functions within broadly 'Western' celebrity culture from three primary perspectives: construction of persona; interactions with audiences and fans; and commodification. Case studies from film and television are used to illustrate the argument that, regardless of their authenticity (real or staged), bromances are useful for engaging audiences and creating an extension of entertainment beyond the film the actors originally sought to promote. The first truly interdisciplinary study of its kind, this book will be of great interest to scholars and students of communications, advertising, marketing, Internet studies, media, journalism, cultural studies, and film and television.